Apixaban Prophylactic Anticoagulation in Patients with Nephrotic Syndrome - Van Meerhaeghe, Tess; Cez, Alexandre; Dahan, Karine; Esteve, Emmanuel; Elalamy, Ismail; Boffa, Jean Jacques; Ponlot, Eleonore (TH Open, 2022)
Background Nephrotic syndrome (NS) is associated with an increased risk of thromboembolic events (TEs), due to hemostatic derangements. The use of direct oral anticoagulants (DOACs) in the prevention of TE has not been studied intensively in patients suffering from NS.Methods The method included retrospective analysis of consecutive incident patients with NS due to glomerular disease, receiving apixaban for thromboprophylaxis. It is an uncontrolled, single-center study.Results We identified 27 patients treated with apixaban for the prevention of TEs, in the context of NS. During follow-up, apixaban minimal blood concentration (trough level; Cmin) and maximum blood concentration (Cmax) levels were measured. The mean duration of the anticoagulant treatment was 153 days (±132). Patients were followed for a mean of 14.7 months (±8.4) since the introduction of apixaban. Three patients had a TE at the time of NS diagnosis. Two patients had pulmonary embolism (PE) and one patient presented a stroke in a lupus membranous nephropathy context. One patient developed PE approximately 2 months after the introduction of apixaban treatment. No minor or major bleeding events were noticed.Conclusion The present study shows that patients, suffering from severe NS under anticoagulant therapy with apixaban had a reduced risk of venous and arterial TEs compared with patients previously described in the literature, without increased risk of bleeding.
Keywords: nephrotic syndrome; anticoagulation; direct oral anticoagulants; thromboembolic event; thromboprophylaxis; hypoalbuminemia